2022
DOI: 10.1021/acs.langmuir.1c03277
|View full text |Cite
|
Sign up to set email alerts
|

Selective Separation of Highly Similar Proteins on Ionic Liquid-Loaded Mesoporous TiO2

Abstract: Separating proteins from their mixtures is an important process in a great variety of applications, but it faces difficult challenges as soon as the proteins are simultaneously of similar sizes and carry comparable net charges. To develop both efficient and sustainable strategies for the selective separation of similar proteins and to understand the underlying molecular mechanisms to enable the separation are crucial. In this work, we propose a novel strategy where the cholinium-based amino acid [Cho][Pro] ion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recently, trace amounts of biocompatible ILs were added into protein−nanostructured TiO 2 SERS substrate systems to adjust their interactions through the dissociation− hydration of ILs and to further promote protein adsorption, allowing an exceptionally low limit of protein detection down to 10 −9 M with high SERS EFs. 18,19 We have reported that a phosphonium-based IL as an additive can enhance the interaction of a protein with TiO 2 nanotube array substrates and also facilitate protein adsorption and thus boost the SERS performance. 15 Nevertheless, to the best of our knowledge, the effect of the composition and structure of ILs, in particular, the chain length of alkyl chains in ILs on the interaction of the probe molecule with the nanostructured SERS substrate and thus the SERS performance, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, trace amounts of biocompatible ILs were added into protein−nanostructured TiO 2 SERS substrate systems to adjust their interactions through the dissociation− hydration of ILs and to further promote protein adsorption, allowing an exceptionally low limit of protein detection down to 10 −9 M with high SERS EFs. 18,19 We have reported that a phosphonium-based IL as an additive can enhance the interaction of a protein with TiO 2 nanotube array substrates and also facilitate protein adsorption and thus boost the SERS performance. 15 Nevertheless, to the best of our knowledge, the effect of the composition and structure of ILs, in particular, the chain length of alkyl chains in ILs on the interaction of the probe molecule with the nanostructured SERS substrate and thus the SERS performance, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike organic solvents, ionic liquids (ILs) are good alternative additives to change the microenvironment and to regulate the protein–SERS substrate interactions. ILs are organic salts composed of organic cations and either organic or inorganic anions with a melting point of <100 °C; depending on the structure and size of the cation and anion, many ILs are liquid at ambient temperature and can potentially replace organic solvents. Recently, trace amounts of biocompatible ILs were added into protein–nanostructured TiO 2 SERS substrate systems to adjust their interactions through the dissociation–hydration of ILs and to further promote protein adsorption, allowing an exceptionally low limit of protein detection down to 10 –9 M with high SERS EFs. , We have reported that a phosphonium-based IL as an additive can enhance the interaction of a protein with TiO 2 nanotube array substrates and also facilitate protein adsorption and thus boost the SERS performance . Nevertheless, to the best of our knowledge, the effect of the composition and structure of ILs, in particular, the chain length of alkyl chains in ILs on the interaction of the probe molecule with the nanostructured SERS substrate and thus the SERS performance, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%